Urbanização, turismo e seus impactos nos recursos naturais no município de Ilhabela - SP - Diniz, Tales de Deus [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The urbanization process in the Brazilian cities is directly linked to its main economic activities, and causes several impacts on the natural resources. It can be seen at the city of Ilhabela, an archipelago located at the north coast of the state of São Paulo, that still has a great area of preserved Atlantic Rainforest, and where today the tourism is the main economic activity. With this in sight, this paper aimed to make a prospect of the current situation of the city, looking at the main aspects of its economic and urban development and the environmental impacts related to them. Among the aspects studied, are the irregular occupations at preservation areas on the island: the pressure on the sea ecosystems by the fishing and the boat circulation, and at the beaches by the tourists flow. Were also observed the characteristics of the city’s urban infrastructure, such as the water supply, sewer and road networks and the waste collecting. Finally, it was analyzed the way that the government acts over the preservation of the island’s natural resources, by the Municipality and the Ilhabela State Park, so that the acting of these two agents could be compared

O processo de urbanização das cidades brasileiras está diretamente ligado às suas principais atividades econômicas, e causa diversos impactos nos recursos naturais. Isso pode ser observado no município de Ilhabela, arquipélago localizado no litoral norte do estado de São Paulo, que abriga uma grande área de Mata Atlântica preservada, e onde atualmente o turismo é a principal atividade econômica. Com essa perspectiva, procurou-se elaborar um panorama da situação em que a cidade se encontra, observando os principais aspectos de seu desenvolvimento econômico e urbano e os impactos ambientais a eles relacionados. Entre os aspectos analisados, estão as ocupações irregulares em áreas de preservação na Ilha; a pressão nos ecossistemas marinhos pela pesca e circulação de navios; e nas praias pelo fluxo de turistas. Também observou-se as características da infraestrutura urbana do município, como as redes de abastecimento de água e coleta de esgoto, a malha viária e a coleta de resíduos. Por fim foi analisada a forma como o Poder Público atua na conservação dos recursos naturais da Ilha, através da Prefeitura Municipal e do Parque Estadual de Ilhabela, podendo ser comparada a atuação desses dois organismos
Keywords: Turismo; Urbanização; Impacto ambiental; Ilhabela (SP) - Aspectos ambientais; Recursos naturais